Physical-chemical characterization of local maize from Chiapas, Mexico - Guevara-Hernández, Francisco; Hernández-Ramos, Manuel; La O-Arias, Manuel; Pinto-Ruíz, René; Rodríguez-Larramendi, Luis; Raj Aryal, Deb (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
The physical-chemical quality of maize has become important for the food industry, so it is a condition for the selection of any local cultivar or improved varieties. The physical-chemical quality of local maize from La Sepultura Biosphere Reserve (REBISE), Chiapas, was characterized, to demonstrate that the maize diversity in the reserve presents potential for the flour and tortilla industry in Mexico. Collections of eighteen local maize populations associated with different races and two commercial hybrid materials were evaluated. Nineteen variables were characterized using multivariate techniques of Factor Analysis and Clusters. By reduction of data, six components were extracted. Typology of maize varieties merged into four groups: Group I) Of high projection in the components of  breaking strength (Fu Rup RE, 300.25 gf) and pericarp dissolution (pericarp, 5.39 %; retained pericarp, 47.91 %); Group II) also high scoring in breaking strength and its persistence (Fu Rup RE, 277.25 gf), but low scoring for grain consistence and protein yield (flotation index  24.50); weight of 100 grains 33.31 g, (grain proteins 9.94 %); Group III) presented greater projection in the component of grain density, and moisture of the nixtamal and the dough (hectoliter weight 73.5 kg-hl, elongation 13.60 mm, dough moisture 57.95 %, Fu Rup RE, 220.83 gf); Group IV) showed lower projection in nixtamal moisture (44.48 %) and dough, so as elasticity of the tortillas (12.94 mm). The physical-chemical variables contributed to identify cultivar groups on the quality of the grain.